Purna Kalasha (pot of fertility) - Mumbai Archive Project Team (Jio Institute, 2024)
The purna kalasha (pot of fertility) consists of a pot traditionally made of metal such as copper, brass, silver, or clay. It is filled with water, and five or more fresh mango leaves are placed around the neck. A whole coconut is placed on top, nestled among the mango leaves. The purna kalasha symbolizes fertility and is used in Hindu ceremonies to bless new beginnings.